Effect of Pre-Weld Sand Blasting on Residual Stress Distribution in Ship Steel Using Magnetic Barkhausen Noise Technique (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This paper aims at investigating the effect of preweldsandblasting on residual stresses distribution in shipsteel plates using magnetic Barkhausen noise (MBN)technique. The measurements have been conducted along aline crossing the weld as a function of distance from theweld bead at the back of the plate. Four tests have beenperformed in the experiment in four conditions. The asreceived,sand blasted, as received-welded and the sandblasted–welded plates are tested. The as-received plateshows a statistically constant Barkhausen noise levelindicative of the specimen processing history. The sandblasted plate shows a similar Barkhausen noise behavior butof lower intensity. The welded specimen shows a pattern ofthe Barkhausen response characteristic of the heat affectedzone (HAZ) as a result of residual stresses redistribution.The sand blasted-welded specimen shows also a similarpattern but of lower intensity. The difference in the inducedsignals is attributed to the impedance and accumulation ofresidual compressive stresses due to sandblasting. The resultindicates that the resultant residual tensile stresses at theheat affected zone could be reduced by using pre-weldsandblasting process.